Criminal law policies on activities obstacing the management of Infectious diseases - Mutmainnah; Muhadar; Abd. Assist (The International Journal of Politics and Sociology Research, 2023)
The goals of the research include looking at (1) how criminal law approaches behaviors that impede the control of infectious disease epidemics and (2) how such activities are punished. Specifically, a normative statutory approach (statute approach) to legal research is used. Peulis gathers information for her studies by reading widely. Legal research is a method of inquiry that places a premium on statutory and regulatory texts as primary sources. Primary and secondary sources of information are used. Standardized research methodologies are used to evaluate the outcomes of literature reviews, which are then methodically organized and evaluated. The findings demonstrated that (1) Indonesian criminal law contains the criminal law policy towards activities to obstruct the control of infectious disease outbreaks in Law Number 4 of 1984 concerning outbreaks of infectious diseases and Law Number 6 of 2018 concerning health quarantine, and (2) activities to obstruct the management of the outbreak are punishable by imprisonment and fines under Law Number 4 of 1984 concerning infectious disease outbreaks. Overall, researching criminal law policies on activities obstructing the management of infectious diseases is urgent to enhance public health protection, prevent harm, promote behavior change, ensure effective response and preparedness, and address ethical and human rights considerations. The findings from this research can inform policymakers, legal professionals, public health authorities, and other stakeholders in developing and implementing evidence-based measures to safeguard public health during infectious disease outbreaks.